Halophilic bacteria as potential pyrite bio-depressants in Cu-Mo bioflotation. (1st January 2020) - Luque Consuegra, Guillermo; Kutschke, Sabine; Rudolph, Martin; Pollmann, Katrin
Highlights: Adhesion to pyrite occurs only by hydrophobic bacteria (Halomonas sp. And Halobacillus sp.). Biodepression of pyrite is observed by all halophilic bacteria to different extents. Best biodepressants are Halomonas boliviensis, Halobacillus sp. and Halomonas sp. Bacteria adsorb onto pyrite surface when a high adhesion to hydrocarbons is observed. Abstract: Five halophilic bacteria have been studied as potential pyrite biodepressants. Microflotation experiments, as well as hydrophobicity and adhesion experiments were performed in order to assess the potential of these bacteria in the sulfide flotation process. It was shown that bacteria with hydrophobic properties in the Microbial Adhesion To Hydrocarbons (MATH) test adhere to pyrite and that Halomonas boliviensis and Halomonas sp. adhere to chalcopyrite in artificial sea water medium. Selective pyrite biodepression was greatly enhanced in the presence of Halobacillus sp. and Halomonas sp., and Halomonas boliviensis whilst chalcopyrite flotation was unaffected and in fact, enhanced by Halobacillus sp. Marinobacter spp. and Marinococcus sp. showing that the potential of this family of bacteria is yet to be untapped and could be an interesting development in sulfide bioflotation/biodepression processes.